(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Because of their high rates of morbidity and death, displaced femoral neck fractures in older individuals provide a serious orthopedic issue. Improving patient outcomes and quality of life requires effective management of these fractures. When compared to alternative therapies, total hip arthroplasty (THA) is thought to be a favorable surgical procedure that offers better functional results and fewer complications. Objective: The goal of total hip replacement is to ascertain the early functional result for older patients who have displaced femoral neck fractures. Methods: From December 2024 to April 2025, sixty patients with displaced femoral neck fractures, ages 50 to 80, received complete hip replacements at , Gujranwala Teaching Hospital Gujranwala (GTH)as part of this descriptive study. Radiographs and several blood tests were part of the preoperative evaluations. Six months after surgery, the Harris Hip Score (HHS) was used to gauge functional results. SPSS version 26 was utilized for data analysis, and preoperative and postoperative HHS ratings were compared using the paired t-test; P < 0.05 was deemed significant. Results: Results – The sixty patients’ average age was 65±9.08 years. At the six-month follow-up, the mean preoperative HHS of 72.55±10.5 had dramatically increased to 86.65±8.65 (P = 0.0001). and three individuals (5%), hip dislocations. Fifty-five patients (91.7%) showed no signs of problems. Conclusion: For older patients with displaced femoral neck fractures, total hip arthroplasty is a successful operation that shows a low incidence of complications and notable improvements in functional results.